ASUHAN KEBIDANAN PADA NEONATUS NY “S” DI RUMAH BERSALIN BUNDA PUJA TEMBILAHAN TAHUN 2019 - Nanda Ariska; Haryati Astuti (STIKES HUSADA GEMILANG, 2020)
Neonates is the first period of life outside the womb up to the age of 28 days. Infant mortality rate (Kemenkes, 2018) in Indonesia 185 / day, The Neonatal Mortality Rate 15 per 1000 live births. Based on The Public Health service Profile (2019) the number of neonate deaths in Indragiri Hilir Regency as many as 21 neonate deaths and a complete KN of 79.9% means that it has not reached the minimum service standar target. The purpose of neonate obstetrics care is to conduct examinations and find out as early as possible if there are health problems in neonates. This midwifery upbringing to provide care to the neonates of Mrs.